The role of social capital and labour exchange in the soils of Mediterranean Chile. Issue 2 (4th May 2017) - Infante, Felipe
Abstract : The unirrigated Mediterranean region of Central Chile is characterised by high levels of soil degradation and rural poverty. One of the main institutional approaches to these issues have mainly focused on promoting the forest industry's entrance along with the introduction of agricultural machinery and more efficient agricultural methods. These have been sponsored as an answer for the needed development, which, in most cases, is far from being suited to the ecological and cultural contexts. This article analyses the main historical and sociocultural factors behind this socio-environmental issue, emphasizing how qualitative factors related to the loss of social capital and the disintegration of communities have had fundamental implications for the environmental problem of soil degradation. Finally, it examines regional social dynamics and traditional agricultural activities that propose social cohesion and territorial empowerment as the bases for sustainable agriculture in environmentally vulnerable regions.